Electron spin resonance studies on magnetoresistive (La0.67Ca0.33)MnO3 compound - (:unkn) unknown (ELSEVIER, 2004)
Electron spin resonance (ESR) measurements have been carried out on colossal magneto-resistive (La0.67Ca0.33)MnO3 thin films deposited on single-crystalline alumina substrate by laser ablation technique. Both, the resonance field value and line shape in ESR spectra were observed to exhibit strong temperature dependence between 4 and 300 K. Significant absorptions appeared at low fields as well. The ESR spectra at low temperature were seen to consist of overlapping low-energy spin wave resonance (SWR) modes excited across opposite surfaces of the film. The SWR data were analyzed by using a magnetic energy density including usual Zeeman and exchange terms contained both in bulk and surface anisotropy energies. The magnetic parameters, such as magnetization, exchange stiffness, relaxation and exchange anisotropy energy, have been deduced as a function of temperature between 4 and 300 K by fitting the simulated spectra to the experimental ones. It was found that quite strong exchange anisotropy is induced consistent with spins canting to give smaller magnetization due to the Dzyaloshinsky-Morya (D-M) interaction in perhaps spin glass-like phase at low temperature. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: colossal magnetoresistivity; manganites; ESR; exchange anisotropy; DOUBLE EXCHANGE; GIANT-MAGNETORESISTANCE; TEMPERATURE-DEPENDENCE; WAVE RESONANCE; ANISOTROPY; ESR; MAGNETIZATION; DYNAMICS; FILMS; POLARONS